Manding-English Dictionary : Maninka, Bamana Vol. 1. - Vydrin, V. F. (Valentin Feodosʹevich) (Book collections on Project MUSE., 2015)
Manding is a common name for several closely related languages in West Africa: Maninka (or Malinke), Bamana (or Bambara), Jula, Mandinka, Xasonka, etc., spoken by up to 40 million people. In this dictionary, forms of Malian Bamana and Guinean Maninka are included. The polysemy of words is represented in all details, the senses are represented hierarchically. Verbal valencies are indicated throughout and clarified by abundant illustrative examples. Numerous idiomatic expressions are given. Most of lexemes are provided with etymological information: sources of borrowing or proto-forms and their reflexes in other Mande languages. The dictionary is oriented toward advanced language learners and professional linguists, but it can be also useful for native speakers of Bamana and Maninka languages.